Statistic model of speech-like signal generation - Paweł BIEŃKOWSKI; Wojciech MYŚLECKI (Archives of Acoustics)
This paper presents a parametric model of a generator of a signal with probabilistic characteristics of a speech signal. Optimal parameters of the model have been selected for a case of a Polish speech signal and research results of the model in the form of a computer programme are given.